2006
DOI: 10.1108/13552510610685093
|View full text |Cite
|
Sign up to set email alerts
|

The inter‐organizational relationship in a multi‐contractor business network

Abstract: This paper presents a study on the relationship between the client and the contractor in a multi-contractor business network. A model built on transaction cost economics and relational exchange theory is proposed to determine the preferred governance mechanism as a function of fit with the technical environment of facilities management. Hypotheses in the model are tested by means of data collected from a survey of facilities managers. The dependent variable is relational norm (defined as degree of relational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Bailey et al [1] reported that 70 % of the companies in their research sample had outsourced one or more of their business functions. Gradually the outsourcing practice has extended to more and more important functions [4]. Consequently an increasing demand for a variety of industrial services has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Bailey et al [1] reported that 70 % of the companies in their research sample had outsourced one or more of their business functions. Gradually the outsourcing practice has extended to more and more important functions [4]. Consequently an increasing demand for a variety of industrial services has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Bailey et al (2002) reported that 70 percent of the companies in their research sample had outsourced one or more of their business functions. Gradually the outsourcing practice has extended to more and more important functions (Harland et al, 2005;Hui and Tsang, 2006). Consequently an increasing demand for a variety of industrial services has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…The risks of outsourcing have been addressed in previous research (Al-Turki, 2011;Campbell, 1995;Hui and Tsang, 2006;Leavy, 2001;Murthy et al 2002). However, the perspective has concentrated on just one company, usually the customer.…”
Section: Striving For Win-win Situations In Maintenance Networkmentioning
confidence: 99%
“…Previous studies include numerous cost models for maintenance (Alsyouf, 2006;Hui and Tsang, 2006;Dekker, 1996;Garg and Deshmukh, 2006;Komonen, 2002;Oke, 2005;Sharma et al, 2011;Salonen and Deleryd, 2011;Tam and Price, 2008). There is still a need for pragmatic models which integrate the qualitative and quantitative perspectives, as well as the maintenance network point of view.…”
Section: Introductionmentioning
confidence: 99%